Orbita oka. Melancholia wzroku w Sedanie Pawła Hertza i w Drewnianym koniu Kazimierza Brandysa - Kozłowska , Izabela (Przestrzenie Teorii, 2020)
The article concerns the way in which the eye topos functions in Paweł Hertz’s Sedan and Kazimierz Brandys’ The Wooden Horse, works representing Polish literature of retribution written in the 1940s. The role of the process of seeing is interpreted by means of the category of melancholy, and the protagonists in these works are presented as melancholics. Standing in front of a window or in the quiet of European museums, members of the intelligentsia do not so much focus on passive contemplation but rather protest against History. The desire to constantly use the eyes has an existential and political sense. Recognition of the phenomenon of a melancholic gaze in the literature of retribution enriches the traditional interpretation of this trend in literature by lending it a new context and allowing rehabilitation of the intellectuals portrayed in it.